[Group Around Suitcases at Landmannalaugar] - Streng, Evelyn Fiedler (1975)
Photograph of a group of people standing around suitcases on a rocky beach. The group dig through the contents of the suitcase, some people knelt down while other stand. A white and light blue vehicle is visible in the top right corner of the photograph. Grey rocks sit on the beach, forming a mountain in the top left corner of the photograph.